Biomimetic Surface Coatings from Modular Amphiphilic Proteins - Wan, Fan (Université d'Ottawa / University of Ottawa, 2014)
Engineering of biofunctional scaffolds to precisely regulate cell behavior and tissue growth is of significance in regenerative medicine. Protein-based biomaterials are attractive candidates for functionalization of scaffold surfaces since the ability to precisely control protein sequence and structure allows for fine-tuning of cell-substrate interactions that regulate cell behavior. In this thesis, a series of de novo proteins for bio-functionalization of interfaces was designed, synthesized, and studied. These proteins are based on a diblock motif consisting of a surface-active, amphiphilic block β-sheet domain linked to a disordered, water-soluble block with a terminal functional domain. Several types of functional domains were investigated, including sequences that act as ligands for cell surface receptors and sequences that act as templates for the growth of inorganic particles. Under moderate temperature and pH conditions, the amphiphilic β-sheet block was shown to have a strong affinity to a variety of scaffold materials and to form stable protein coatings on hydrophobic materials by self-assembly. Moreover, the surface adsorption of the proteins was shown to have minimal impact on the presentation of the functional end domains in the soluble block. For the case of diblocks with the RGDS integrin binding sequence, the capability for mediating cell attachment and spreading was demonstrated via control over ligand density on hydrophobic polymer surfaces. The case of diblock proteins with templating domains for inorganic materials was investigated for two systems. First, hydroxyapatite-binding domains were ligated to the end terminus of the water-soluble block to develop proteins for possible bone regeneration applications. It was demonstrated that the hydroxyapatite-binding domain had strong affinity to hydroxyapatite nanoparticles and was able to induce calcium phosphate mineralization on the surfaces coated with diblock proteins from dilute solutions with Ca2+.and PO43-. Next, a silver-binding domain was ligated to the end terminus to create a diblock protein for potential antimicrobial surface applications. The silver-binding domain was shown to accumulate and reduce silver ions, resulting in the formation of silver nanoparticles on the surfaces functionalized by the protein.
Keywords: Surface functionalization; Protein-based biomaterials; Self-assembly; Protein coatings; Cell-substrate interactions